Automated upper dipper by Sensing light intensity - Raut, Chandni; Dhok, Komal; Jha, Parul (International Journal of Computer Sciences and Engineering, 2025)
Automatic upper dipper using light dependent resistor(LDR) while driving a vehicle in the night many drivers do not dip the head lamps of their vehicles in night while approaching. Several switching operation is used to dip the head light which may distract the concentration. one of the essential safety feature that need to be installed is automatic upper dipper control of headlight. Headlight of vehicles pose a great danger during night driving. The drivers of most vehicles use high, bright beam while driving at night. This causes a discomfort to the person travelling from the opposite direction and therefore experiences a sudden glare for a short time this is caused high intense headlight beam from the other vehicle coming towards the one from the opposite direction. In this project an automatic headlight dimmer which use a light dependent system (LDR) sensor has been designed to dim the headlight of on-coming vehicles to avoid human eye effected. This automatically switches the high beam into low beam, therefore reducing the glare effect by sensing the light intensity value approaching vehicle and also eliminates the requirement of manual switching by the driver which was not done at all time.